2015
DOI: 10.1016/j.juro.2014.10.094
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Modified Z Trendelenburg Position on Intraocular Pressure during Robotic Assisted Laparoscopic Radical Prostatectomy: A Randomized, Controlled Study

Abstract: Our results suggest that modifying the Trendelenburg position during robot-assisted laparoscopic radical prostatectomy has a significant positive effect on patient neuro-ocular safety by lowering intraocular pressure and accelerating its recovery to the normal range without affecting the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…To the best of our knowledge, the present study was the first and largest prospective study to evaluate IOP and visual field sensitivity during RALP in the patients with ocular diseases. We showed that IOP significantly increased during TP in RALP in a time‐dependent manner, as previously described . Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To the best of our knowledge, the present study was the first and largest prospective study to evaluate IOP and visual field sensitivity during RALP in the patients with ocular diseases. We showed that IOP significantly increased during TP in RALP in a time‐dependent manner, as previously described . Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range. At 7 days after RALP, IOP returned to near preoperative levels, as previously described . Interestingly, IOP in patients with ocular diseases, even with glaucoma, changed by the same amount as healthy patients; this is in contrast to a previous study that reported dramatic elevation in IOP among patients with glaucomatous or vascular eye disease .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Raz et al applied a modified Z-TP during RALP and found a significant positive effect on patient neuro-ocular safety by lowering intraocular pressure without any negative effects on surgery. Increased IOP can also be reduced by drugs [19]. In a study by Molloy et al, 32.5% of patients undergoing lengthy laparoscopic surgery in STP had an IOP higher than 40 mmHg [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies highlighting POVL and markedly elevated IOP changes (reaching glaucomatous range) after laparoscopic surgery had been performed with steep Trendelenburg position or in prolonged procedures. 1214,19,21,22,24,25 Mondzelewski et al 22 observed a significantly elevated IOP in patients undergoing robot-assisted laparoscopic procedures in steep Trendelenburg position compared with IOP in those undergoing laparoscopy or open procedures in a horizontal position, further highlighting the role of positioning over and above that of pneumoperitoneum in significant IOP elevations. A recent study performed among patients undergoing laparoscopic colorectal surgery showed greater IOP elevation in both eyes of patients in Trendelenburg position during the surgical procedure, but found no substantial difference between the Trendelenburg and non-Trendelenburg group when IOP was measured 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%